Independent Conditional Clauses In the French Language - Lejla Tekešinović (Društvene i Humanističke Studije, 2025)
The paper examines independently composed clauses in the French language in which the semantic relation of conditionality is recognized. These sentences are two-part, coordinated, and juxtaposed sentence structures that differ typologically. Therefore, the main goal of this paper is to determine the types of sentences involved, identify their basic grammatical and semantic features, and then explore specificities that emerge in certain contexts during the semantic interpretation of such sentence structures. 6 types of conditional independently composed clauses are distinguished according to the basic syntactic-semantic features of the first clause, which in these two-part structures is the carrier of conditional semantics, which was confirmed in all the above examples by paraphrases in which a dependent conditional clause replaces the first clause with the conjunction si.